Enhancing Vocational Education in China: The Impact of Design Thinking on Curriculum Reform and Talent Development - Gao Hetian; Fauzi Naeim (International Journal of Education and Humanities, 2025)
China's vocational education strives to enhance its curriculum quality and optimize its structure to cultivate innovative talents. However, traditional approaches focus more on problem-solving than developing user-centered solutions, which may hinder innovation. This study explores the application of design thinking as the primary approach to improving the talent training model and curriculum structure in China's vocational education. Design thinking is considered to foster the development of innovative skills through a more solution-focused and user-centric approach. The study involved 46 participants at Shaoguan Technician College, Guangzhou Province, China. Participants participated in an experimental course designed to cultivate their design thinking abilities. The diary method was employed to track and record the learning process of the participants, allowing the researchers better to understand the impact of design thinking on their development. The findings show that the implementation of design thinking positively impacts the reform of the vocational education curriculum system. The new curriculum model based on design thinking significantly stimulated the participants' enthusiasm for learning. Moreover, participants improved their innovation, creativity, observation, and teamwork skills throughout the learning process. The vocational institutions in China adopt design thinking in their curricula. This is crucial for fostering talents adept at solving problems and innovating in response to real-world challenges.